PEPTONE EXTRACTION OF YELLOW PIKE CONGER (CONGRESOX TALABON) PROCESSING WASTE AS A MEDIUM GROWTH NUTRITIONAL MICROORGANISMS - Boy Laoli; Sukirno '; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in March-April 2015 in the Laboratory of Fish Processing Technology, Laboratory of Microbiology and Biotechnology, Faculty of Fisheries and Marine Sciences, University of Riau, Laboratory of Analytical Chemistry, Faculty of Mathematics and Science, University of Riau and the Laboratory of Chemical Physics, Faculty of Mathematics and Science, University of North Sumatra. This study aims to produce peptone from waste yellow pike conger entrails as bacterial nutrients to support the growth of bacteria in the growth medium. Waste yellow pike conger entrails autolysis hydrolysed by activating proteolytic enzymes (pepsin) in the stomach of fish using 12 N HCl at pH (1,2,3 and 4) the hydrolysis temperature 40oC for 24 hours to determine the optimum hydrolysis conditions. The optimum hydrolysis conditions of waste yellow pike conger entrails occurs at pH 3, the temperature of 40oC hydrolysis with hydrolysis time of 24 hours, the solution was centrifuged extract peptone hydrolysis and then dried with a freeze dryer. The results showed peptone fish entrails have cunang content of 79.06% protein content; total nitrogen 12.66%; free α-amino nitrogen 1.97%; the ratio AN / TN 15.56%; water content of 5.43% and 93.03% solubility in water. Growth of test bacteria Escherichia coli ATCC 8739 and Staphylococcus aereus 6538 showed peptone yellow pike conger entrails can be used as a nutrient growth of bacteria on the growth medium.Keywords : Peptone, yellow pike conger, autolysis, enzyme pepsin, E. coli ATCC 8739, S. aereus 6538